EMPLOYEE WELLBEING AND SUSTAINABLE WORKPLACE - Nadzrah Yusof,; Salmi Mohd Isa,; Goh Yen Nee, (Journal of Islamic, Social, Economics and Development, 2022)
The concept of well-being in the context of one's place of employment is increasinglybeing brought up in mainstream organisational research. The focus of this paper is on thefactors that are connected with one's well-being in their place of employment, and it alsoaddresses two organising frameworks for the conceptualization of well-being at workplace.This paper aims to discuss the importance of employee wellbeing in creating a sustainableworkplace. The paper draws on the various literature sources to create a conceptual model foremployee wellbeing and sustainable workplace. Using the mini-review analysis it is found thatthe psychological factors significantly affect employee's well-being. Also, the employee's wellbeinghas a significant effect on job performance. A major impact on an employee's overallwell-being can be attributed to psychological variables. Additionally, the health and happinessof the worker has a substantial bearing on their performance at work